Assessing think tank influence in the context of social media: A systematic literature review - Wang, Chenlin; Shen, Jing (Information Research an international electronic journal, 2025)
Introduction. Social media has changed the global political landscape and modes of national social governance. Think tanks are expected to capitalise on the opportunity to amplify their influence on policymakers and the public through social media platforms. This study aims to explore how to assess think tanks’ influence in social media and to identify the focuses, key framework, measures, and metrics employed in existing research. Method. This paper presents a systematic literature review on the evaluation of think tank influence in the context of social media, following the PRISMA guidelines. Analysis. Characteristics, research topics and evaluation processes are explored through content analysis, statistical analysis, and citation analysis of thirty-two screened articles. Results. The field of think tank influence evaluation has evolved from policy influence assessment to Website, online, and social media influence evaluation, utilizing various indicators and methods. However, a comprehensive and systematic evaluation system is still lacking. Based on the limitations of current studies, we propose three future directions: evaluating the national think tank ecosystem; constructing an influence indicator system using Altmetrics and user-generated content (UGC); and incorporating AI technology in influence evaluation. Conclusion. These findings offer new avenues for enhancing the measurement of think tank influence in a digitally connected world.